1996
DOI: 10.1128/aac.40.12.2749
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of KRM-1648, a new benzoxazinorifamycin, in rats and dogs

Abstract: The pharmacokinetics of 3'-hydroxy-5'-(4-isobutyl-1-piperazinyl) benzoxazinorifamycin (KRM-1648) in rats and dogs given a single oral dose of 3, 30, or 100 mg/kg of body weight were studied. In the rats, the concentrations of KRM-1648 in plasma, whole blood, and tissues peaked between 2.0 and 24.0 h, with elimination half-lives ranging from 6.2 to 19.5 h. The peak concentrations and the areas under the concentration-versus-time curves (AUC) for whole blood and tissues were 2 to 277 times higher than those for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 28 publications
(26 reference statements)
0
14
0
Order By: Relevance
“…Rifalazil and its metabolites were analysed by hplc according to the method described previously (Hosoe et al 1994, 1996b, Mae et al 1996 with slight modi® cations. The isocratic mobile phase used in the present study was acetonitrile} citrate perchlorate buå er (1} 1 v} v) and the peaks were detected at 620 and} or 230 nm.…”
Section: Hplc Analysis Of Rifalazil and Its Metabolitesmentioning
confidence: 99%
“…Rifalazil and its metabolites were analysed by hplc according to the method described previously (Hosoe et al 1994, 1996b, Mae et al 1996 with slight modi® cations. The isocratic mobile phase used in the present study was acetonitrile} citrate perchlorate buå er (1} 1 v} v) and the peaks were detected at 620 and} or 230 nm.…”
Section: Hplc Analysis Of Rifalazil and Its Metabolitesmentioning
confidence: 99%
“…61 In-vivo activity KRM has high tissue levels but low plasma levels in mice after oral administration, as is also the case with RBT, whereas RFP has high levels in both plasma and tissues. 116,130 AUCs were in the order KRM Ͼ RFP Ͼ RBT for lungs, KRM Ͼ RBT Լ RFP for spleen, RFP Ͼ KRM Ͼ RBT for liver, RFP Ͼ KRM Ͼ RBT for kidney, and RFP Ͼ KRM Լ RBT for plasma. Moreover, KRM had a longer time of elimination from tissues than did RFP and RBT, particularly in lungs and spleen, and exhibited non-linear kinetics of elimination.…”
Section: In-vitro Activitymentioning
confidence: 99%
“…The pharmacokinetics of rifalazil were studied in rats and dogs, after intravenous and oral administration [7]. Rifalazil distributes readily to tissues, as reflected in a large volume of distribution in animals [7]. Given the low doses used in human clinical trials with a therapeutic dose at 25 mg, and a long terminal half-life at above 100 h observed in humans [5], it was important to develop a more sensitive assay in order to perform detailed pharmacokinetic studies.…”
Section: Introductionmentioning
confidence: 99%
“…Bioanalytical methodology for rifalazil has previously been described by Hosoe et al [6,7] for determination of rifalazil concentrations in plasma, whole blood, urine and tissue from rats and dogs. Solid phase extraction and liquid chromatography with UV detection was used for rat plasma with a lower limit of quantification (LLOQ) of 10 ng/mL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation